Memorandum of understanding between Universiti Teknologi MARA and Sekolah Tinggi Pariwisata Bogor / Fakulti Pengurusan Hotel & Pelancongan - Universiti Teknologi MARA, Fakulti Pengurusan Hotel & Pelancongan (Universiti Teknologi MARA (UiTM), 2021)
Memorandum of understanding on friendship and cooperation, promotion of mutual understanding, academic, cultural and scientific thought and personnel exchange.